2013
DOI: 10.1007/s11695-013-1005-0
|View full text |Cite
|
Sign up to set email alerts
|

A New Endoscopically Implantable Device (SatiSphere) for Treatment of Obesity—Efficacy, Safety, and Metabolic Effects on Glucose, Insulin, and GLP-1 Levels

Abstract: The device might be short-term effective in reducing body weight, which might be mediated through alterations in incretin metabolism. However, frequent device migration necessitates device modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…They also showed that these results resolved and significantly improved over 70% of all co-morbidities [ 34 ]. Another endoluminal mechanical device, the SatiSphere (Endosphere Inc., Columbus, OH, USA), is also implanted into the stomach and duodenum to delay the transit time of food and has shown effective short-term results in the treatment of obesity and metabolic disease [ 35 ].…”
Section: Role Of Malabsorptive Endoscopic Procedures In Obesity Treatmmentioning
confidence: 99%
“…They also showed that these results resolved and significantly improved over 70% of all co-morbidities [ 34 ]. Another endoluminal mechanical device, the SatiSphere (Endosphere Inc., Columbus, OH, USA), is also implanted into the stomach and duodenum to delay the transit time of food and has shown effective short-term results in the treatment of obesity and metabolic disease [ 35 ].…”
Section: Role Of Malabsorptive Endoscopic Procedures In Obesity Treatmmentioning
confidence: 99%
“…Additionally, the device was associated with delayed glucose absorption, insulin secretion and altered GLP-1 kinetics. 70 Device migration occurred in 10 of 21 study arm patients, with two necessitating emergent surgery. European study is currently ongoing.…”
Section: Small Bowel Endoscopic Proceduresmentioning
confidence: 99%
“…One study evaluating 21 SatiSphere patients was prematurely terminated due to high migration rates (the device migrated in 10 patients, requiring 2 laparoscopic operations) [24].…”
Section: Space-occupying Devicesmentioning
confidence: 99%